LEGAL NATURE OF BITCOIN - Dąbrowska, Justyna (Człowiek w cyberprzestrzeni, 2020)
The examination of juridical nature the bitcoin is an urgent issue given two circumstances: first, no cryptocurrency legislation is in place neither in EU nor in the Polish law, and second, the bitcoin "currency" is establishing its place in trade. In order to answer the question about the legal nature of bitcoin, its constitutive features must be defined and compared vis-à-vis civil and financial law institutions governed by legal precepts.